2016
DOI: 10.1039/c6ra22603e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of novel 1,2,3-triazole-linked quinoxaline scaffold via copper-catalyzed click reactions

Abstract: New 1,2,3-triazoles-linked quinoxaline, were prepared by the reaction of 2-chloro-3-(prop-2-ynyloxy)quinoxaline or 2,3-bis(prop-2-ynyloxy)quinoxaline with aromatic azides via copper-catalyzed click reactions in the presence of the Schiff base ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…We have successfully applied the copper click reaction for the construction of structures from 1,2,3-triazolelinked heterocyclic moieties. [34,35] In this study, we reported an efficient protocol for the synthesis of new 1,2,3-triazole-linked quinazoline framework (5 and 7) from the reaction of ethyl 4-oxo-3-(prop-2-yn-1-yl)-3,-4-dihydroquinazoline-2-carboxylate and related carboxamide derivatives (3) with aryl azides (4) catalyzed by copper (II) acetate, in the presence of Sodium 4-amino-5-hydroxy-7-sulfonaphthalene-2-sulfonate as an efficient ligand and in water (L3) (Scheme 1).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We have successfully applied the copper click reaction for the construction of structures from 1,2,3-triazolelinked heterocyclic moieties. [34,35] In this study, we reported an efficient protocol for the synthesis of new 1,2,3-triazole-linked quinazoline framework (5 and 7) from the reaction of ethyl 4-oxo-3-(prop-2-yn-1-yl)-3,-4-dihydroquinazoline-2-carboxylate and related carboxamide derivatives (3) with aryl azides (4) catalyzed by copper (II) acetate, in the presence of Sodium 4-amino-5-hydroxy-7-sulfonaphthalene-2-sulfonate as an efficient ligand and in water (L3) (Scheme 1).…”
Section: Resultsmentioning
confidence: 97%
“…[34,35] In this study, we reported an efficient protocol for the synthesis of new 1,2,3-triazole-linked quinazoline framework (5 and 7) from the reaction of ethyl 4-oxo-3-(prop-2-yn-1-yl)-3,-4-dihydroquinazoline-2-carboxylate and related carboxamide derivatives (3) with aryl azides (4) catalyzed by copper (II) acetate, in the presence of Sodium 4-amino-5-hydroxy-7-sulfonaphthalene-2-sulfonate as an efficient ligand and in water (L3) (Scheme 1). [34,35] In this study, we reported an efficient protocol for the synthesis of new 1,2,3-triazole-linked quinazoline framework (5 and 7) from the reaction of ethyl 4-oxo-3-(prop-2-yn-1-yl)-3,-4-dihydroquinazoline-2-carboxylate and related carboxamide derivatives (3) with aryl azides (4) catalyzed by copper (II) acetate, in the presence of Sodium 4-amino-5-hydroxy-7-sulfonaphthalene-2-sulfonate as an efficient ligand and in water (L3) (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Continuing our studies directed toward an efficient and straightforward synthesis of biologically active molecules based on the quinoxaline ring system, [30,31] we present an efficient strategy for the synthesis of new quinoxaline chalcones from the commercially available calcium carbide through palladiumcatalyzed coupling reactions. Our retro-synthetic analysis for the synthesis of quinoxaline chalcones showed the palladiumcatalyzed cross-coupling reaction of 2-amino substituted-3chloroqunoxalines with propargyl amine, formed in situ from calcium carbide, an aldehyde, and dimethylamine, as the key step to this process.…”
Section: Resultsmentioning
confidence: 99%
“…[18] The ligation of 1,2,3-triazolesa nd quinoxalines as electron-deficient moieties is particularly interesting and CuAAC [19] is as uitable methodology for introducing this moiety.H owever,t he construction of 3-triazolylquinoxalines has only been reported in two publications with very few examples. [20,21] Inspired by our chromogenic MCR concept [22] and our particular interest in highly emission solvatochromic quinoxalines, [12b, 13, 15, 23] we reasoned that 3-triazolylquinoxalines could be accessible by combining the one-pot glyoxylation-alkynylation-cyclocondensation synthesis of 3-ethynylquinoxalines with CuAACi naone-pot fashion ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%